An observational study investigating uniformity of manual body condition scoring in dairy cows - Paul, Abhishek; Bhakat, Champak; Mondal, Santu; Mandal, Ajoy (Indian Journal of Dairy Science, 2020)
Body condition scores (BCS) are very useful for dairy herd management but its reliability and consistency of recordings made by observer have been questioned. Moreover, regular high quality manual body condition scoring of an individual cow is difficult as a routine practice in the farm. This study aimed to find out the agreement in BCS within- and between the classifier. An observational study was conducted in which two assessors independently scored BCS of 43 crossbred animals from one dairy hard. Cohenâ€™s kappa (Ðº) and Spearman’s rho (Ï) was computed to quantify the agreement between observer for overall BCS measurement and only kappa test for different BCS groups (high, medium and low). For overall BCS score Ðº of 0.62 to 0.71 (p<0.001) and 0.68 to 0.74 (p<0.001) were obtained for intraobserver 1 and 2 respectively, such values would be interpreted as moderate agreement. Whereas, the interobserver agreement (Ðº) was found to be low i.e. between 0.52 to 0.60 (p<0.001). However, the Spearman’s rho value was higher in all the cases, indicating good correlation among the individual observers. In addition, kappa value (Ðº) for different BCS groups revealed, a lowest agreement between observers (0.31 to 0.37, p<0.001) and within observers (0.34 to 0.59, p<0.001) for medium BCS group as compared to the other BCS groups. These findings suggest manual Body scoring should be performed by multiple observers with better accuracy in the outcome.